An analysis of the contribution of South African music to Bulawayo popular culture: case of Nketa and Nkulumane youths. - Ncube, Tambulani (Midlands State University, 2018)
Music is central in shaping popular culture for the youth in many societies. This study analyses the contribution of South African music to popular culture among the youth of Nketa and Nkulumane in Bulawayo. Theoretically, the study is informed by identity, uses and gratification and encoding and decoding theories of the media. It adopts a qualitative research approach in conducting the research. The study reveals the different components in which South African music is contributing to popular culture among the youth. Music videos and lyrical content are seen to be the biggest carrier of the culture through the contribution to dance, way of dressing, language and slang, subculture/behaviour and lastly local talent. Prominence of South African music among the youth of Nketa and Nkulumane is also compared to their treatment of local music genres. The research also reveals that tribal differences are main cause for the kind of music preference by youth of Nketa and Nkulumane. Recommendations are made to the government, the music industry in Zimbabwe and also the youth themselves.